Stability-indicating comparative methods using mekc and lc for determination of olmesartan medoxomil - Bajerski, Lisiane (2013)
A stability-indicating method using MEKC was validated for the analysis of olmesartan medoxomil in tablets. Successful separation was achieved using a fused silica capillary (40 cm x 50 μm i.d.); background electrolyte consisted of a combination of 10 mmol L-1 borate buffer and 5 mmol L-1 anionic detergent sodium dodecyl sulfate (95:5; v/v) pH 6.5; hydrodynamic mode at 50 mBar for 5 s; 25 kV separation voltage at 25 ºC; and column temperature 25 ºC with detection at 257 nm. The proposed method, validated following ICH guidelines, was applied to the determination of this antihypertensive with good results compared with an LC method.